ISOLASI FUNGI ENDOFIT PENGHASIL ANTIBIOTIKA PADA ALGA MERAH JENIS GRACILARIA VERRUCOSA SECARA KLT-BIOAUTOGRAFI - Herwin, Herwin (Fakultas Farmasi UMI, 2018)
This research aimed to determine the antibacterial fungi endofitic isolate of Gracilaria verrucosa type Rhodophyta that antibiotic as potential by Bioautography-TLC Method. The result of fungi endofitic isolate, obtained that 7 active isolates and purified by quadrant method on potato dextrose agar medium obtained 5 active isolates (isolate 1, 2, 3, 5, 6). The result of the screening of fungi endofitic isolate by cakram method possessed that the biggest inhibitory zone is isolate 2 and isolate 6 by 25 mm at Streptococcus mutans. The test results of fungi endofitic isolate activity by Bioautography-TLC obtained Rf 0.07 0.23, 0.56, 0.78, 0.81 and 0.94 value actif inhibited Bacillus subtilis, Shigella disentry, Streptococcus mutans and Eschericia coli. And the identification results of the chemical component shown that the actif compound at isolate 2 and isolate 6 given result positif alkaloid.